Satisfaction of sojourner couples residing in Nepal: The mediating role of social support and personal and couple resources. - James, Joan Susan. (University of Ottawa (Canada), 1997)
Improvements in transportation have made it more feasible for families to relocate greater distances, sometimes even to other countries. Although this is now a frequent occurrence, the family dynamics associated with adjusting to a new culture have been virtually ignored by researchers. When investigating sojourner families (families who live in foreign countries), researchers rarely integrate the family stress literature, which focuses on stresses incurred in one's native country, and the sojourner literature, which is based on stresses inherent in living in a foreign country. The aim of the present study was to develop and test a model of intercultural family relocation based on an integration of the family stress and sojourner literatures. The model, based on the Double ABCX model, was tested with expatriate couples $(N=205)$ stationed in Nepal with aid agencies, mission organizations, and corporations. More specifically, personal resources identified in the sojourner literature and traditional family stress mediators were investigated to determine whether they played a significant role in mediating the stress-satisfaction relation. The model was tested using structural equation modeling. The results indicated that personal resources (locus of control and self-esteem) and social support did mediate the stress-satisfaction relation, as hypothesized. The family variables, on the other hand, coherence (confidence and acceptance) and couple resources (communication, adaptability, and cohesion), did not directly influence the stress-satisfaction relation. Even though the Double ABCX model is one of the most popular models in family psychology, it was only partially supported by empirical investigation with the sojourner couples living in Nepal. Thus, the results call into question the model's overall validity and generalizability. Future research will need to address this question by testing the model with families in various contexts.
Keywords: Psychology, Social.